Efficacy of 5% Sodium Chloride Therapy in Reducing Corneal Oedema After Phacoemulsification Cataract Surgery - Indrajati, Christina; Rahmawati, Atik; Suparmi, Suparmi (Indonesian Journal of Medical and Pharmaceutical Science, 2025)
Background: Cataract surgery using the phacoemulsification technique often results in postoperative corneal oedema, which impairs visual acuity and reduces patient satisfaction. This study aims to evaluate the efficacy of 5% sodium chloride eye drops as an initial management for postoperative corneal oedema following phacoemulsification. Methods: This double-blind, multicenter randomised controlled trial involved 228 patients with senile cataracts scheduled for phacoemulsification cataract surgery performed by a single experienced ophthalmologist. Patients underwent preoperative screening and were monitored on days 3 and 10 post-surgery. Visual acuity was measured using Snellen charts, and corneal oedema was clinically assessed with slit-lamp examination. Results: On day 3 post-surgery, the group treated with 5% sodium chloride demonstrated significantly better visual acuity than the control group (p=0.000). By day 10, no significant difference in visual acuity was observed between groups (p=0.413). Additionally, the incidence of corneal oedema was significantly lower in the sodium chloride group on days 3 and 10 (p=0.000). Conclusion: Topical 5% sodium chloride effectively reduces corneal oedema after phacoemulsification, resulting in clinical improvement and better early postoperative visual acuity.